Deacetylation of H4-K16Ac and heterochromatin assembly in senescence - Contrepois Kévin; Thuret Jean-Yves; Courbeyrette Régis; Fenaille François; Mann Carl (Epigenetics & Chromatin, 2012)
Abstract Background Cellular senescence is a stress response of mammalian cells leading to a durable arrest of cell proliferation that has been implicated in tumor suppression, wound healing, and aging. The proliferative arrest is mediated by transcriptional repression of genes essential for cell division by the retinoblastoma protein family. This repression is accompanied by varying degrees of heterochromatin assembly, but little is known regarding the molecular mechanisms involved. Results We found that both deacetylation of H4-K16Ac and expression of HMGA1/2 can contribute to DNA compaction during senescence. SIRT2, an NAD-dependent class III histone deacetylase, contributes to H4-K16Ac deacetylation and DNA compaction in human fibroblast cell lines that assemble striking senescence-associated heterochromatin foci (SAHFs). Decreased H4-K16Ac was observed in both replicative and oncogene-induced senescence of these cells. In contrast, this mechanism was inoperative in a fibroblast cell line that did not assemble extensive heterochromatin during senescence. Treatment of senescent cells with trichostatin A, a class I/II histone deacetylase inhibitor, also induced rapid and reversible decondensation of SAHFs. Inhibition of DNA compaction did not significantly affect the stability of the senescent state. Conclusions Variable DNA compaction observed during senescence is explained in part by cell-type specific regulation of H4 deacetylation and HMGA1/2 expression. Deacetylation of H4-K16Ac during senescence may explain reported decreases in this mark during mammalian aging and in cancer cells.